2017
DOI: 10.15283/ijsc17013
|View full text |Cite
|
Sign up to set email alerts
|

Lineage-specific Expression of miR-200 Family in Human Embryonic Stem Cells during In Vitro Differentiation

Abstract: Although microRNAs have emerged as key regulators in diverse cellular processes, the roles of microRNAs are poorly understood in human embryonic stem cells (hESCs) during differentiation into specialized cell types. In this study, we used a microRNA array with 799 human microRNA probes to examine the expression profiles of microRNAs in hESCs during differentiation into endodermal and mesodermal lineages in vitro. Among the microRNAs analyzed, 7 and 20 microRNAs were enriched in the developmental process of hES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 24 publications
(24 reference statements)
3
10
0
Order By: Relevance
“…MiR‐200c is one of the miRNAs functioning in cell proliferation . It was also reported to promote iPSCs reprogramming and several other lineages differentiation including neurogenesis . Consistently, high expression of miR‐200c in iPSCs was observed in our results.…”
Section: Discussionsupporting
confidence: 90%
“…MiR‐200c is one of the miRNAs functioning in cell proliferation . It was also reported to promote iPSCs reprogramming and several other lineages differentiation including neurogenesis . Consistently, high expression of miR‐200c in iPSCs was observed in our results.…”
Section: Discussionsupporting
confidence: 90%
“…It is well known that the miR-200 family suppresses EMT. It has also been reported that the knockdown of miR-200c inhibits NANOG and up regulates GATA4, thereby inhibiting self-renewal and promoting hESC differentiation [ 88 ]. Transfection with a group of miRNAs including miR-200c, miR-302s, and miR-376s family successfully coaxed somatic cells into an iPSC fate [ 89 ].…”
Section: The Two Big Mirna Families Of Pluripotency: Mir-200 and mentioning
confidence: 99%
“…Although the negative role of Zeb family members in mESC mesendodermal commitment has been reported previously 28 , 53 , 54 , no molecular mechanisms underpinning its repressive function have been elucidated in this model. Zeb1, as EMT regulator, plays a well-recognized role in tumor progression and metastasization 20 , 21 , 23 .…”
Section: Discussionmentioning
confidence: 77%
“…Along with this line of evidence, Liu and coworkers 52 recently reported Zeb1 as important for the positive cardiovascular lineage commitment of human induced pluripotent stem cells (hiPS) or human ESC (hESC). On the contrary, Kim et al 53 provided evidence that Zeb1 downregulation in hESC is an early event during differentiation in endodermal and mesodermal lineages. The latter evidence is supported by our results and by prior work from Luo et al 54 .…”
Section: Discussionmentioning
confidence: 96%